Internal Migration, Center-State Grants and Economic Growth in the States of India - Cashin, Paul (IMF Working Papers; Working Paper, 1995)
This paper examines the growth experience of twenty states of India during the period 1961-91, using cross-sectional estimation and the analytical framework of the Solow-Swan neoclassical growth model. We find evidence of absolute convergence--initially-poor states did indeed grow faster than their initially-rich counterparts. There has also been a widening of the dispersion of real per capita state incomes over the period 1961-91. However, relatively more grants were transferred from the central government to the poor states than to their rich counterparts. Significant barriers to population flows also exist, as net migration from poor to rich states responded only weakly to cross-state income differentials.